Hermite model based estimation of peak factors for tall buildings subjected to wind induced pressures - Keerthana, M.; Harikrishna, P. (Journal of Structural Engineering, 2024)
The peak factor for non-Gaussian fluctuating pressures occurring in the flow separated regions of a rectangular tall building has been evaluated based on three translation based Hermite methods, basic Hermite Model (HM), Revised Hermite Model (RHM) and Modified Hermite Model, with parameters evaluated from Yang (MHM-Yang). The evaluated peak factors have been compared with observed values from the data and other Hermite based models of peak factors available in literature. The relative performance of the models towards evaluation of peak factors, especially in the regions of flow separation have been assessed. It has been observed that use of data driven Hermite based models could provide a better and realistic estimate of peak factor, as compared to that offered by Gaussian framework.